Process Political of Farming Village Regulations (A Case of Study of The Formation of Village Regulation No. 5 Year 2022 on Implementation of Disaster Management in Majalaya Village Bandung Regency) - Bambang Rudiansah (Dinasti Research, 2024)
Village Regulations are legislative rules created by the Village Consultative Body (BPD) together with the village head, which are established by the village head with the purpose of regulating in order to implement higher laws and regulations. The formation of Village Regulations in the case study of the establishment of Village Regulation Number 5 of 2022 concerning Disaster Management in Majalaya Village, Bandung Regency, has not yet reached its targets as of now. Therefore, this research aims to understand the process of formulating policy for village regulations regarding disaster management in Majalaya Village, Bandung Regency. The research method used is a descriptive method with a qualitative approach, and data is obtained through data collection sources such as literature studies, participant observation, in-depth interviews, and documentation. The data sources are obtained from Majalaya Village, the Majalaya Village Consultative Body, the Disaster Management Organization, and the Youth Organization of Majalaya Village. The data collection techniques use primary and secondary data. The research findings indicate that the Political Process of Formulating Village Regulations (Case Study on the Formulation of Village Regulation Number 5 of 2022 concerning Disaster Management in Majalaya Village, Bandung Regency) has not been optimal due to a lack of competent human resources, ineffective socialization, inadequate transparency in decision-making, and a lack of community participation.